The Effect Of Return On Assets, Net Profit Margin, Earnings Per Share, And Dividend Policy On Stock Prices In The Energy Sector On The IDX - Ripa Sriyanti; Joko susilo; Yasir Hudzaifah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Net Profit Margin (NPM), Earnings Per Share (EPS), and Dividend Policy on stock prices in the energy sector listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The method used is panel data regression analysis, utilizing secondary data from annual financial reports. The results show that only the Earnings Per Share (EPS) variable has a significant negative effect on stock prices, while ROA, NPM, and Dividend Policy do not have a significant impact. The research model explains 74.32% of the variation in energy sector stock prices. These findings provide valuable insights for investors to consider corporate financial factors, particularly EPS, when making investment decisions in the energy sector, although other external factors such as government policies and global energy price fluctuations should also be taken into account.